Modalitas Kemenangan Pramono-Rano Pada Pilkada Provinsi Daerah Khusus Jakarta Tahun 2024 - Gaston Otto Malindir (Fakultas Politik Pemerintahan, 2026)
This study aims to analyze and describe the modalities of Pramono-Rano's victory in the 2024 Regional Head Election of the Special Region of Jakarta Province. This study uses a qualitative approach with a constructivist-interpretive paradigm, with the research design used being a qualitative case study. The data collection techniques used in this study include observation and limited participatory interviews. The data analysis technique uses an interactive analysis model that includes three main stages: data reduction, data presentation, and conclusion drawing and verification. Based on the results of the research and analysis above, it can be concluded that Pramono-Rano's victory was influenced by social, economic, cultural, and symbolic capital. This can be specifically explained as: Pramono-Rano's campaign utilized social capital to build trust and direct engagement with various elements of society. Pramono's ability to interact with various groups, including non-party groups such as FBR and Boing Labi, demonstrates the use of inclusive social relationship modalities, expanding the network of political support. Economic capital actually emerged through the management of various resources, ranging from funds, energy, time, to ideas that were implemented jointly by the team and party cadres. Meanwhile, cultural capital is not only reflected in Pramono-Rano's intellectual capacity, but also in his ability to understand and bring to life local Betawi cultural values. Pramono-Rano's symbolic capital was formed through a long process involving experience, public recognition, and ongoing social trust.